Analysis of the contribution of ergonomics to the management system and organizational governance - Yparraguirre, Ivany Terezinha Rocha; Zotes, Luis Perez; Leal Filho, Walter; Lima , Gilson Brito Alves (Brazilian Journal of Operations & Production Management, 2023)
The purpose is To analyze the application of ergonomics in management systems and organizational governance demonstrating the relevance of the potential of its application. The methodology is marked by three major stages. The first is the identification of scientific texts that address the theory of ergonomics. The second is the identification of reports of experiences of application of ergonomics. In the third, the content analysis of the identified scientific texts is carried out and the discussion of the results obtained contributing to organizational theory and practices. The findings come from literature review methods and secondary data from case studies. It concludes that the organizational culture should value the application of ergonomics in projects. The contributions of ergonomics to the management system, compliance and organizational governance are described. The main limitations present in the research are inherent to the chosen methods, that is, the Bibliographic Review does not cover all the possibilities of application of the concepts of ergonomics to the management system and to governance. The conclusions, finally, go through the subjectivity of the researcher in the analysis of the peculiarities of the case studies identified and cited. The main contributions of this work are focused on the support and guidance of organizational practices for the management system and good governance practices. The academic contribution consists of the ergonomic analyzes articulated and aggregated to the management system and organizational governance. Originality is supported by the governance and management system approach under the ergonomics guideline.